Please Call Me John: Name Choice and the Assimilation of Immigrants in the United States, 1900-1930 - Pedro Carneiro; Sokbae Lee; Hugo Reis (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2016)
The vast majority of immigrants to the United States at the beginning of the 20th century adopted first names that were common among natives. The rate of adoption of an American name increases with time in the US, although most immigrants adopt an American name within the first year of arrival. Choice of an American first name was associated with a more successful assimilation, as measured by job occupation scores, marriage to a US native and take-up of US citizenship. We examine economic determinants of name choice, by studying the relationship between changes in the proportion of immigrants with an American first name and changes in the concentration of immigrants as well as changes in local labor market conditions, across different census years. We find that high concentrations of immigrants of a given nationality in a particular location discouraged members of that nationality from taking American names. Poor local labor market conditions for immigrants (and good local labor market conditions for natives) led to more frequent name changes among immigrants.
Keywords: J15; N32; 330; Americanization; culture; first name; identity; immigration